DER FACHBEZOGENE FREMDSPRACHENUNTERRICHT AN POLNISCHEN HOCHSCHULEN (1953-1989) - Harbig, Anna Maria (Neofilolog, 2020)
This article describes the origin and development of the teaching of foreign languages for special purposes in Polish schools of higher education. The time frame in question runs from the setting up of Foreign Language Centers to the turning point year, 1989. The conditions, aims and methods of conducting classes with students of non-philological courses are presented in the context of the development of methodology for teaching foreign languages for special purposes in Poland. The picture is supplemented with an analysis of handbooks for teaching German for special purposes, used in the 80s in classes at the Foreign Language Center, the University of Białystok.